Effect of niobium on thermal stability and impact toughness of Nd-Fe-B magnets with ultra-high intrinsic coercivity - 胡志华 刘国军 王会杰 (Journal of rare earths, 2011)
The effects of Nb on the thermal stability and impact toughness of ultra-high intrinsic coercivity of Nd-Fe-B magnets were investigated.The results showed that the addition of Nb could improve the thermal stability,and obviously increased the impact toughness of sintered Nd-Fe-B magnets.The optimum thermal stability of sintered Nd-Fe-B magnets was obtained when the content of Nb was 1.0 at.%.The maximum impact toughness of sintered Nd-Fe-B magnets was obtained when the content of Nb was 1.5 at.%,but the magnetic properties of sintered Nd-Fe-B magnets drastically deteriorated when the content of Nb increased from 1.0 at.% to 1.5 at.%.The microstructure showed that overfull Nb addition made many ultra-fine grains get together,which led to the density of sintered Nd-Fe-B magnets decline and drastically deteriorated the magnetic properties of sintered Nd-Fe-B magnets.